Catastrophic health expenditure among cancer patient attending Bhaktapur cancer hospital. - Khanal,Niharika (2020)
ABSTRACT: Background: High out of pocket expenditure results in catastrophic health expenditure either pushing the individuals and households into poverty or preventing them from accessing the health care. Currently, the lack of financial protection in health is considered to be a major problem in the health systems. This study aimed to estimate the catastrophic health expenditure, its associated factors and coping strategies of cancer patient. Methods: A hospital based cross sectional study was conducted in two hundred and eighty cancer patients attending Bhaktapur cancer hospital. Semi-structured pretested questionnaire was used for data collection. Face to face interview technique was conducted. Descriptive, bivariate (Chi square, ttest and Mann Whitney test) and multivariate analysis were performed to find out the association between catastrophic health expenditure and independent variables. Results: Overall 91.4% of the respondents incurred catastrophic health expenditure. The mean total OOP healthcare expenditures of those who faced catastrophic was NRs 770,496.68 with standard deviation of 375,556.63 NRs. Family consisting of children under 5 years of age were 0.070 times less likely to suffer catastrophic health expenditure (95% CI: 0.007 - 0.728; p value 0.026). The patients used household saving to pay for their illness, borrowed money from relatives, friends or bank, sold their assets and some of them received the amount from social health insurance to cope up their treatment cost. Conclusion: A substantial proportion of hospitalized patients were exposed to catastrophic health expenditure. Family consisting children under five years were less likely to incur catastrophic. Different coping strategies were adopted by the cancer patients. Mechanisms that pool risk and cost are needed to ensure better access and high degree of financial protection against the impact of illness. Keywords: Out of pocket expenditure, catastrophic health expenditure, cancer